2019
DOI: 10.3390/molecules25010023
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium-Depleted Water as Adjuvant Therapeutic Agent for Treatment of Diet-Induced Obesity in Rats

Abstract: In this study, we present the potential application of deuterium-depleted water (DDW) for the prevention and adjuvant treatment of obesity in rats. We tested the hypothesis that DDW can alleviate diet-induced obesity (DIO) and its associated metabolic impairments. Rats fed a high-fat diet had an increased body weight index (BWI), glucose concentration, and level of certain proinflammatory cytokines; decreased levels of insulin in the serum; decreased tryptophan and serotonin in the brain, and a decreased conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
0
20
0
5
Order By: Relevance
“…In further experiments on laboratory animals, it is necessary to study the effect of low concentrations of deuterium on the functioning of various fat depots in various physiological and pathological situations (stress, high-fat diet, etc.) 83,84 .…”
Section: Discussionmentioning
confidence: 99%
“…In further experiments on laboratory animals, it is necessary to study the effect of low concentrations of deuterium on the functioning of various fat depots in various physiological and pathological situations (stress, high-fat diet, etc.) 83,84 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studied the metabolism of the symbiotic organism medusomycetes (tea fungus) and the influence of D 2 O on its development [ 51 ]. Recent studies on the effects of low concentrations of deuterium on rats and mice show that the organism accelerates its metabolism [ 43 , 52 , 53 , 54 ]. In this regard showed that one could use ddw water to test inhibitors of de novo lipogenesis (DNL) by performing back-to-back studies in higher species, treat nonhuman primates with platensimycin, an inhibitor of fatty acid synthase [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…is could be considered as the so-called shock (functional) effect [28,[36][37][38][39] when the culture is transferred from one growth medium to another. However, redistribution of deuterium and protium in intracellular structures probably leads to a gradual adaptation of the culture to the new D/H isotope ratio.…”
Section: Cell Viability Assessment With Trypan Blue Dye After Cultivamentioning
confidence: 99%